Eco-friendly strategic goals and the performance of innovative green processes: The impact of green intellectual capital - Esponda Pérez, Jorge Alberto (2025)
The purpose of this study is to check the intellectual capital's role in shaping green process innovation. This article contends the company's capacity to create, possess, incorporate, and implement environmentally friendly intellectual assets in its activities will result in a higher degree of performance in terms of innovative green processes. This performance serves as an indicator of the company's enduring dedication to an environmentally conscious strategy. The industries chosen for this studycomprised textile, chemical, pharmaceutical, and steel based in Mexico. The random sampling technique was used to gather data. Upon analyzing the gathered data, we used only 253 questionnaires for analysis, representing a response rate of 42.7%. Findings indicate green strategic intent significantly influences three components of intellectual capital: human, relational, and organizational capital. Three components of intellectual capital significantly influence green process innovation. A green strategy can be successfully implemented by the implementation of intangible resources. Mere tangible resources are insufficient to gain superior green innovation performance; the interaction of these two resources (tangible and intangible) is complementary. Companies are adopting environmental strategies to mitigate the environment's harmful impact and meet stakeholders' demands. The study’s practical implications aim to improve companies’ environmental performance, specifically their green performance, through the implementation of green innovation.